Exploring recreational fishers' perceptions, attitudes, and support towards a multiple-use marine protected area six years after implementation. (November 2016) - Martin, Carol L.; Momtaz, Salim; Jordan, Alan; Moltschaniwskyj, Natalie A.
Abstract: This study assessed the acceptance and awareness of an Australian MPA (Port Stephens-Great Lakes Marine Park) post implementation by recreational fishers using the MPA, and identified factors that influenced the perception of this group towards the MPA. Recreational fishers were interviewed in a multiple-use MPA to investigate their perceptions, attitudes, and support towards the MPA six years after implementation. Almost two thirds of recreational fishers supported the MPA and had positive attitudes towards the concept of MPAs. This is a key result since a similar pre-implementation survey of recreational fishers found only 12% would support the creation of PSGLMP due to fears the MPA would negatively impact their fishing activities and ability to catch fish. However, there was a sub-group of fishers who opposed the MPA and were more inclined to have negative attitudes towards the rationale behind MPAs, despite the common perception that no-take zones were for fisheries management purposes and could increase fish stocks in the MPA. More experienced fishers were inclined to oppose the MPA, as well as fishers who believed management zones did not provide clear rules for activities, penalties for non-compliance were too harsh, or that no-take zones did not increase fish stocks. An important perceived threat to the MPA was from commercial fishing due to perceptions of over-exploitation and issues of non-compliance. In contrast, the majority of recreational fishers did not believe the collective actions of recreational fishers negatively impacted the marine environment and fish stocks, or the number of fish available for capture in the future. An improved understanding of these social aspects is important to target ongoing management in order to increase acceptance, success and long-term existence of MPAs.